Upadacitinib Salvage Therapy for Infliximab-Experienced Patients with Acute Severe Ulcerative Colitis - Robert Gilmore; Wei Lian Tan; R Fernandes; Yoon‐Kyo An; Jakob Begun (2023)
Abstract Background and Aims Acute severe ulcerative colitis [ASUC] is a medical emergency treated with intravenous steroids followed by infliximab or cyclosporin in the case of steroid failure with emergent colectomy required in refractory or severe cases. Case series have reported on the effectiveness of tofacitinib for refractory disease, but data regarding the effectiveness of upadacitinib in this setting have not been previously reported. We describe the use of upadacitinib therapy for steroid-refractory ASUC in patients with prior loss of response to infliximab. Methods Six patients who received upadacitinib for steroid-refractory ASUC were identified at two Australian tertiary inflammatory bowel disease centres. Patients were followed for up to 16 weeks after discharge with clinical, biochemical and intestinal ultrasound [IUS] outcomes. Results All six patients demonstrated clinical response to upadacitinib induction during their inpatient admission. Four patients achieved corticosteroid-free clinical remission by week 8, including complete resolution of rectal bleeding and transmural healing assessed by IUS, and sustained clinical remission at week 16. One patient proceeded to colectomy at week 15 due to refractory disease. No adverse events directly attributable to upadacitinib were identified. Conclusions Upadacitinib may have a role as a safe and effective salvage therapy for steroid-refractory ASUC in patients who have previously failed to respond to infliximab therapy. Prospective studies are required to determine the safety and efficacy of upadacitinib use in this setting before routine use can be recommended.